2006
DOI: 10.1080/13694670500440684
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and affective resolution following a stressful event: General and religious coping as possible mediators

Abstract: The current study replicated and extended previous research on mediators of attachment qualities and outcome (affective resolution), including appraisal, coping, and religious coping. Structural equation models were used to analyze the responses on an Internet survey for a primarily Christian sample of 1,289 adults (416 men and 873 women). As expected, appraisal was a significant mediator of ambivalent attachment qualities and coping, as well as ambivalent attachment qualities and religious coping. Avoidance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
4
29
1
Order By: Relevance
“…Zwingmann et al [126] presented data that suggested that the effects of religious coping on psychosocial adjustment in breast cancer patients were fully mediated by non-religious coping strategies, and Pérez et al [127] found that spiritual striving and depressive symptoms was mediated by acceptance. Burker et al [128], on the other hand, reported findings that religious coping strategies do not appear to be functionally redundant when predicting stress in lung transplant candidates, as did Schottenbauer et al [17] in a large survey of respondents self-identifying as Christian. Other evidence for the unique contribution of religious coping strategies comes from Jermann et al [129], who investigated the effects of mindfulness on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zwingmann et al [126] presented data that suggested that the effects of religious coping on psychosocial adjustment in breast cancer patients were fully mediated by non-religious coping strategies, and Pérez et al [127] found that spiritual striving and depressive symptoms was mediated by acceptance. Burker et al [128], on the other hand, reported findings that religious coping strategies do not appear to be functionally redundant when predicting stress in lung transplant candidates, as did Schottenbauer et al [17] in a large survey of respondents self-identifying as Christian. Other evidence for the unique contribution of religious coping strategies comes from Jermann et al [129], who investigated the effects of mindfulness on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As with the item-level analyses, the samples were very diverse, and the sample sizes varied from 71 [52] to 1289 [17], with a mean of 288.70. Twelve studies [17,18,[52][53][54][55][56][57][58][59][60][61] reported that the turning to religion sub-scale loaded to a factor with at least one other sub-scale, three studies [62][63][64] reported that the turning to religion sub-scale formed its own separate factor, and five studies [21,[65][66][67][68] reported that the religion sub-scale did not have a sufficiently high loading with any other factor. As with the item-level analyses (Table 1), PCA was the most frequently used technique, with 9 of the 20 studies [18,[52][53][54]56,57,62,64,66] explicitly stating this method.…”
Section: Studies That Conducted Their Own Exploratory Factor Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It may be that spirituality and hope are two constructs that work in parallel to facilitate coping and adjustment. Religious coping is highly beneficial in low-control situations (e.g., coping with the life-threatening nature of the child’s illness), whereas hope-thought and problem-focused coping may be more beneficial in high-control situations (e.g., giving the child medicine to alleviate treatment side effects; Schottenbauer, Dougan, Rodriguez, Glass, & Arnkoff, 2006). Therefore, spiritual growth in the context of parenting a child with cancer may be independent of dispositional hope.…”
Section: Discussionmentioning
confidence: 99%